Who responds more to monetary policy, conventional banks or participation banks? - Macit, Fatih (2012)
In this paper I investigate whether there is a systematic difference between conventional banks and participation banks in terms of their response to monetary policy shocks. For this purpose I look at the quarterly loan growth of commercial banks and participation banks in Turkish banking sector and see whether the lending channel of monetary policy differs depending on bank type. At the same time, I control for some bank specific variables, namely the log of real assets, the ratio of liquid assets to total assets and the ratio of equity to total assets. I find that participation banks show larger reaction to monetary policy. In terms of bank specific variables, banks with higher liquidity ratio tend to have higher loan growth, whereas banks with larger asset size have smaller loan growth. DOI: https://doi.org/10.1016/S2077-1886(12)70003-3